Validation of PIN 3 physical activity survey in low-income overweight and obese young mothers - Chang, Mei-Wei (BMC Public Health, 2015)
BACKGROUND: Existing physical activity surveys have not been validated for use with low-income overweight and obese young mothers. This study aimed to validate the Pregnancy Infection and Nutrition 3 (PIN3) physical activity survey and to explore whether its validity varied by race/ethnicity and body mass index (BMI) category when including or excluding child and adult care activities in the target population. METHODS: Participants were recruited from the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) and were asked to fill out the PIN3 survey and wear an Actigraph accelerometer. Validity was assessed (N = 42) using Spearman correlation coefficient. RESULTS: Regardless of inclusion or exclusion of child and adult care activity, the PIN3 survey showed evidence of validity for moderate (correlation coefficients 0.33 [p = 0.03]; 0.40 [p = 0.08]) but not vigorous (−0.01 [p = 0.91]; −0.06 [p = 0.69]) physical activity. The mean minutes per week spent in moderate, vigorous and moderate-vigorous physical activity measured by the PIN3 were substantially higher than when measured by accelerometer, for example, 588 (PIN3) versus 148 (accelerometer) minutes per week. Also, correlations between self-reported and objective monitored activity varied substantially by race/ethnicity and BMI category, for example, 0.29 (p = 0.18) for overweight women versus 0.57 (p = 0.007) for obese women; 0.27 (p = 0.20) for African American versus 0.66 (p = 0.001) for white. CONCLUSIONS: The PIN3 survey may be adequate for many applications where quick and practical assessments are needed for moderate physical activity data in low-income overweight and obese young mothers. The substantial differences in mean minutes per week between the PIN3 and accelerometer may be due to over-reported physical activity by the study participants. TRIAL REGISTRATION: Clinical Trials Number: NCT01839708